A Resuscitation Option for Upper Airway Occlusion Based on Bolus Transtracheal Lung Inflation. Issue 4 (9th August 2018) - Villiere, Sophia; Nakase, Ko; Kollmar, Richard; Arjomandi, Hamid; Lazar, Jason; Sundaram, Krishnamurthi; Silverman, Joshua B.; Lucchesi, Michael; Wlody, David; Stewart, Mark
Abstract : Background: Acute laryngospasm sufficient to cause obstructive apnea is a medical emergency that can be difficult to manage within the very short time available for establishing an airway. We have presented substantial evidence that laryngospasm‐based obstructive apnea is the cause of sudden death in epilepsy, and airway management is particularly challenging during seizure activity. Objective: We sought to determine if the transtracheal delivery of a bolus of oxygen or room air below the level of an obstruction to inflate the lungs could be an effective method to prolong the time available for responders seeking to establish a stable airway, and, if so, what could be learned about optimization of delivery parameters from a rat model. Methods: Rats were fitted with a t‐shaped tracheal tube for controlling access to air and for measuring airway pressures. After respiratory arrest from simulated laryngospasm, bolus transtracheal lung inflation with a volume of gas equivalent to half the vital capacity was delivered to the closed respiratory system as the only resuscitation step. Results: Bolus lung inflation was sufficient for resuscitation, improving cardiac function and re‐establishing adequate oxygen status to support life. Inflation steps could be repeated and survival times were approximately 3 times that of non‐inflated lungs. Conclusion: The properties and consequences of bolus lung inflation are described as a foundation for procedures or devices that can be useful in cases of severe laryngospasm and other cases of upper airway obstruction. Level of Evidence: 3